The relationship between traditional authorities and municipal councillors and its impact on local development: A Case study of the AmaNdebele Ndzundza Sokhulumi community - Phakathi, Mpumelelo (My University, 2018)
This study explores the relationship between traditional authorities and municipal ward councillors, in a democratic South Africa. The conflict between customary law and the Constitution of South Africa. The focus of this study is to investigate how this relationship impacts on local development of traditional communities by observing different government structures within the community who are responsible to bring about local development and services delivery. The objective is to understand and observe the process of how different components within this community relate, looking at the obvious and imperceptible factors which interfere with the functioning of the institutions. The interest of this research is centred on understanding how the interface between traditional authorities and municipal ward councillors is expressed at local sphere of government. This study is based on detailed empirical work obtained through first hand research in KwaSokhulumi Traditional Community, using the case study design. This study is qualitative in natured and used in-depth, structured and unstructured interviews to collect data. This was beneficial to this study as it provided complex textual descriptions of how community members and leaders experienced the dual system of governance within their community. Further, providing information about the human side of an issues such as beliefs, emotions, behaviours, opinions and how they relate to these institutions. The methods used were effective in identifying intangible facts, such as social norms, gender roles, socioeconomic status, tradition and culture. This study found that the relationship between traditional authorities and municipal ward councillor is not good and it is complicated by the fact the Constitution and other municipal Acts do not stipulate what are the roles of traditional authorities in local government. Worsened by the overlap in roles of traditional authorities and municipal ward councillor. This study also found that legitimacy contributes to the tension because both these institutions understand legitimacy different. Lastly, Hierarchy, of who comes first or who has the mandate to develop the community was a stumbling block to local development and resulted in breakdown in the relationship. The impacts of this tension are obvious and can be seen/experienced in the community of Sokhulumi. There is a breakdown in trust between community members, traditional authorities and municipal ward councillor. This study found out that developmental projects are delayed because of this breakdown of relationship and contestation of power.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies in Faculty of Humanities, University of the Witwatersrand, Johannesburg, June 2018
Keywords: Tribal government--South Africa; Local government--South Africa